Can We Boost Treatment Adherence to an Online Transdiagnostic Intervention by Adding Self-Enhancement Strategies? Results From a Randomized Controlled Non-inferiority Trial - Isbăşoiu, Andreea Bogdana; Tulbure, Bogdan Tudor; Rusu, Andrei; Sava, Florin Alin (Frontiers in Psychology, 2021)
Using a two-armed randomized non-inferiority trial design, the present study compared the modified version (self-enhanced) of the 9-session Transdiagnostic Unified Protocol (9UP) with a previously validated internet delivered protocol (Tulbure et al., 2018, Barlow et al., 2011) as an active control. Our main prediction was that both groups produce significant alleviations of the outcomes and that the self-enhanced 9UP is non-inferior to the 9UP on all primary outcomes. In addition, as a consequence of the newly added self-related assignments, we also expected that participants engage in completing these new tasks to a higher frequency than the original ones, increasing the level of treatment adherence. As a secondary, rather exploratory, objective, we tested if the self-enhanced 9UP produces significantly higher augmentations to the self-concepts targeted by the newly added exercises (e.g., self-esteem, self-compassion), than the standard protocol. The intervention group (baseline n = 142) received the self-enhanced nine modules of the unified protocol (Self-enhanced 9UP) while the active control (baseline n = 142) received the standard nine modules (9UP). The newly added techniques were inspired by the acceptance and commitment therapy and were specific for self-concepts such as self-compassion or unconditional self-acceptance. Both programs lasted for 9 weeks. The non-inferiority of the Self-enhanced 9UP was tested against a margin of d = .35, on the following primary outcome measures: depression; generalized anxiety, social phobia, and panic. The dropout rates were similar in both groups (approximately 45%) and high overall. We failed to increase treatment adherence, but we found support for the non-inferiority hypothesis. Hence, the alterations performed to the 9UP protocol, although they did not boost the treatment attractiveness, also did not decrease the treatment effectiveness as suggested by most non-inferiority analyses. Likewise, the gain on self-concepts was produced by both groups. The short version of the Unified Protocol seems to have the potential of effectively alleviating a larger palette of psychological variables associated with mental health symptoms than previously known.